Professionals Evaluating Clients' Suitability for Digital Health and Social Care: Scoping Review of Assessment Instruments - Anu-Marja Kaihlanen; Lotta Virtanen; Emma Kainiemi; Tarja Heponiemi (JMIR Publications, 2023)
BackgroundIncreased digital health and social care services are generally considered to improve people's access to services. However, not everyone can equally access and use these resources. Health and social care professionals should assess clients' suitability for digital solutions, but to succeed, they need information about what to evaluate and how. ObjectiveThis scoping review aimed to identify evaluation tools that professionals can use when assessing clients' suitability for digital health and social care. We summarized the dimensions and the practical usefulness of the instruments. MethodsThe MEDLINE (Ovid), CINAHL, Web of Science, and ASSIA databases were searched in February 2023 following the Joanna Briggs Institute's Manual for Evidence Synthesis. Studies were included if they focused on health and social care clients and professionals, examined clients' suitability for using digital health or social care, and applied related assessment methods in the direct client work of professionals. Studies focusing primarily on instruments intended for research use without clear applicability to professionals' practical contexts were excluded. Details of the eligible studies were extracted, and qualitative content analysis according to the research objectives was performed. ResultsA total of 19 articles introducing 12 different assessment instruments intended for the health care context were included in the review. No instruments were found for evaluating the suitability for digital social care. The instruments contained 60 dimensions of the client's suitability for digital health, which reflected four perspectives: (1) skill-based suitability, (2) suitability based on general ability to maintain health, (3) suitability based on attitude and experience, and (4) suitability based on practical matters. The described practical usefulness of the instruments included professionals' possibility to (1) identify clients most in need of education and support, (2) direct and recommend the right clients for the right digital services, (3) ensure that clients can use digital health, (4) improve effectiveness and maximize the provision of digital health, (5) develop and redesign services, and (6) empower clients. ConclusionsBased on the diverse assessment instruments available and the dimensions they measure, there seems to be no comprehensive evaluation tool for assessing clients' prerequisites to use digital solutions. It is important to further develop comprehensive screening tools applicable to professionals' busy work (both in health and social care) with defined threshold values for suitability.